Peripheral Precocious Puberty of Ovarian Origin in a Series of 18 Girls: Exome Study Finds Variants in Genes Responsible for Hypogonadotropic Hypogonadism - Brauner, Raja; Bignon-Topalovic, Joelle; Bashamboo, Anu; McElreavey, Ken (Frontiers in Pediatrics, 2021)
Background: Peripheral precocious puberty of ovarian origin is a very rare condition compared to central form. It may be associated with an isolated ovarian cyst (OC). The causes of OC in otherwise healthy prepubertal girls is currently unknown. Methods: Exome sequencing was performed on a cohort of 18 unrelated girls presenting with prenatal and/or prepubertal OC at pelvic ultrasonography. The presenting symptom was prenatal OC in 5, breast development in 7 (with vaginal bleeding in 3) and isolated vaginal bleeding in 6. All had OC ≥ 10 mm. The girls had no other anomalies. Four patients had a familial history of ovarian anomalies and/or infertility. Results: In 9 girls (50%), candidate or known pathogenic variants were identified in genes associated with syndromic and non-syndromic forms of hypogonadotropic hypogonadism including PNPLA6, SEMA3A, TACR3, PROK2, KDM6A, KMT2D, OFD1, GNRH1, GNRHR, GLI3, INSR, CHD7, CDON, RNF216, PROKR2, GLI3, LEPR. Basal plasma concentrations of gonadotropins were undetectable and did not increase after gonadotropin-releasing hormone test in 3 of them whilst 5 had prepubertal values. The plasma estradiol concentrations were prepubertal in 6 girls, high (576 pmol/L) in one and not evaluated in 2 of them. Conclusions: In the first study reporting exome sequencing in prepubertal OC, half of the patients with OC carry either previously reported pathogenic variants or potentially pathogenic variants in genes known to be associated with isolated or syndromic forms of congenital hypogonadotropic hypogonadism. Functional studies and studies of other cohorts are recommended to establish the causality of these variants.